2014
DOI: 10.1002/ajmg.a.36630
|View full text |Cite
|
Sign up to set email alerts
|

Cutis laxa with pulmonary emphysema, conjunctivochalasis, nasolacrimal duct obstruction, abnormal hair, and a novel FBLN5 mutation

Abstract: We report on a 4-year-old girl with autosomal recessive cutis laxa, type IA, or pulmonary emphysema type (ARCL1A; OMIM #219100), with loose and wrinkled skin, mitral and tricuspid valve prolapse, conjunctivochalasis, obstructed nasolacrimal ducts, hypoplastic maxilla, and early childhood-onset pulmonary emphysema. Mutation analysis of FBLN5 showed a homozygous c.432C>G missense mutation, and heterozygosity in the parents. This is predicted to cause amino acid substitution p.Cys144Trp. Conjunctivochalasis or re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
10
1
Order By: Relevance
“…Callewaert et al and other investigators have reported pulmonary emphysema and vascular complications as two main characteristics of ARCL type I (10,11). However, our case with the novel homozygous mutation has limited segments, with pulmonary emphysema and no vascular involvement.…”
Section: Discussioncontrasting
confidence: 48%
“…Callewaert et al and other investigators have reported pulmonary emphysema and vascular complications as two main characteristics of ARCL type I (10,11). However, our case with the novel homozygous mutation has limited segments, with pulmonary emphysema and no vascular involvement.…”
Section: Discussioncontrasting
confidence: 48%
“…Hereditary CL includes X‐linked CL (XRCL; MIM: 304150), autosomal dominant CL (ADCL; MIM:123700), and autosomal recessive CL (ARCL). To date, 12 different causative genes have been identified: ATP7A responsible for XRCL (i.e., occipital horn disease) and 11 associated with the two autosomal inheritance patterns, including ATP6V1A , ATP6V1E1 , ELN , FBNL5 , FBNL4 , LTBP4 , ATP6V0A2 , PYCR1 , ALDH18A1 , GORAB , and RIN2 (Basel‐Vanagaite et al, 2009; Baumgartner et al, 2000; Hennies et al, 2008; Kantaputra & Kaewgahya, 2014; Kornak et al, 2008; Markova et al, 2003; Reversade et al, 2009; Urban et al, 2009; Van Damme et al, 2017; Van Damme, Gardeitchik, & Mohamed, 2017; Van Maldergem et al, 1988; Zhang et al, 1999). Of the three genetic forms of CL, ARCL is usually associated with the most severe phenotype and include three main subtypes: ARCL1 caused by FBLN5 (i.e., ARCL1A), EFEMP2/FBLN4 (i.e., ARCL1B) and LTBP4 (i.e., ARCL1C); ARCL2 due to ATP6V0A2 (i.e., ARCL2A), PYCR1 (i.e., ARCL2B), ATP6V1E1 (i.e., ARCL2C) and ATP6V1A (i.e., ARCL2D); and ARCL3 (a.k.a., De Barsy syndrome) caused by ALDH18A1 (i.e., ARCL3A) and PYCR1 (i.e., ARCL3B).…”
Section: Introductionmentioning
confidence: 99%
“…The FBLN5-related CL is inherited in an autosomal dominant and recessive manner (Van Maldergem and Loeys, 1993). Autosomal recessive cutis laxa (ARCL), type IA, is more severe than the autosomal dominant form and characterized by loose and wrinkled skin, childhood-onset emphysema, aortic and pulmonary artery stenosis, inguinal hernia, and diverticula of the intestine or bladder (Kantaputra et al, 2014). Here, we report a family with a novel missense mutation in the FBLN5 gene.…”
Section: Introductionmentioning
confidence: 98%